A Record of Palaeo-Tsunami in the Indian Ocean - K. A. Kumar ; H. Achyuthan (Marine Geodesy, 29: 253-263, 2006, 2006)
The history of catastrophic events on the Indian coast helps us to understand the frequency and magnitude of the tsunamis that occurred in the Indian Ocean. These catastrophic events have changed the coastal landscape and have left significant records for further studies. These rare events have occurred in the Indian Ocean. There have been megatsunamigenic events in the past due to volcanic eruptions and earthquakes. Those events due to earthquakes have proved more catastrophic than the volcanic activities. There has been limited official records of the causality and magnitude of palaeotsunamigenic events. These have been studied using the various proxies. The rate of sedimentation is a proportional tool to study the magnitude of a tsunami and this has proved to be a successful tool along with foraminiferal assemblages. Causes for a tsunami to occur are by and large, the subduction zone earthquakes of the Indian plate has been the most common source for tsunami in the Indian Ocean. More often the Andaman and Nicobar and the Indonesian islands have been vulnerable to tsunami than the mainland of India and Sri Lanka. In summary, in the last 200 years at least three basin-wide tsunamis have occurred, with several smaller tsunami affecting one or more coastlines in the region. The December 2004 M-9 tsunami seems to have been the largest and most destructive in the last two centuries, suggesting most tsunami are likely to be smaller but still allowing the possibility that even larger tsunami could be generated in propitious circumstances.